2019
DOI: 10.1016/j.juro.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Older Age Predicts Biopsy and Radical Prostatectomy Grade Reclassification to Aggressive Prostate Cancer in Men on Active Surveillance

Abstract: For men on AS, older age at time of diagnosis was positively associated with BGR to GG≥3, and RPGR. These observations imply that for many older men, AS (as opposed to watchful waiting) remains a more appropriate management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…However, the older patients were reported to have more aggressive prostate cancer at diagnosis more frequently [3]. And age is also considered as a risk factor of pathological upgrading to higher risk disease after operation [4]. In older men with high-risk disease, the aggressive treatment with a 46 % reduction of mortality risk was reported comparing to treat conservatively [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, the older patients were reported to have more aggressive prostate cancer at diagnosis more frequently [3]. And age is also considered as a risk factor of pathological upgrading to higher risk disease after operation [4]. In older men with high-risk disease, the aggressive treatment with a 46 % reduction of mortality risk was reported comparing to treat conservatively [3].…”
Section: Discussionmentioning
confidence: 99%
“…20 Men aged >70 on active surveillance are also at increased risk of progression (n=1625). 21 In our own local audit of 500 TRUS results from 2010 to 2013, we found that approximately 70% of all high-grade cancer occurs in men >70. This perhaps explains why the European screening trial only reduced mortality by 20%.…”
Section: Discussionmentioning
confidence: 89%
“…Druskin et al (page 98) from Baltimore, Maryland evaluated a cohort of 1,625 men on active surveillance to determine the influence of patient age on reclassification to a Gleason score of Grade Group 3 or higher cancer. 8 The 5-year incidence of reclassification to Grade Group 3 or higher was 4%, 7% and 14% for ages less than 60 years, 60 to 69 years and 70 years or greater, respectively. The impact of age was retained on multivariable analysis.…”
Section: Age Predicts Grade Reclassification To Aggressive Prostate Cancermentioning
confidence: 90%